Blended Learning sebagai Metode Pembelajaran Inovatif pada Pelatihan Cardiopulmonary Resuscitation (CPR) - Linda Widyarani (Jurnal Keperawatan Notokusumo, 2015)
One of the emergency cases which is a major cause of death was cardiac arrest. Relief is given to patients with cardiac arrest is an act of Cardiopulmonary Resuscitation (CPR). Nurses must have the competence to perform CPR to engage themselves in training BTCLS. Currently the training is done by conventional methods but the resulting output is less than optimal. This study aimed to examine the effectiveness of blended learning as an innovative teaching methods in the implementation of CPR training. Through a data base search method EBSCHost, Science direct, Medscape, Proquest, and PubMed from 2010-2014, using related keywords. Selection of the RCT criteria and fulltext. Showed that the blended learning method is shown to have a higher success rate than conventional methods (face-to-face) or computer-based methods (e-learning). Learners are more active and longer retention of science proven, flexible and cost-efficient over time. It was concluded that the blended learning as an innovative teaching methods in the implementation of CPR training is more effective than conventional methods and computer-based methods (e-learning).